Quran Memorizing Interactive Application For Autistic Children - Muhammad Izzat, Mohamad Rizal (2022)
This proposed project aims to develop an interactive application to assist autistic children in memorizing the Quran. The application will utilize visual aids, audio recordings, and repetition exercises tailored to the learning needs of autistic children. Through the use of interactive features, the application seeks to enhance engagement, recall, and comprehension of the Quranic teachings. The project will involve testing and evaluation to ensure its effectiveness, with the potential to contribute valuable insights to the fields of Islamic education and autism research. Ultimately, this project strives to provide a unique and effective tool for autistic children to learn and memorize the Quran, promoting their religious involvement and fostering their educational development.